EFFECT OF CLIMATE CHANGE ON THE PREVALENCE OF HYPERTENSIVE DISORDERS IN PREGNANCY AND ITS COMPLICATIONS - Umer, Sana; Malli, Pushpa; Heeramani,; Khan, Momna; Akhtiar, Reema; Paras, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Preeclampsia and gestational hypertension are the two forms of hypertensive diseases of pregnancy that are a significant cause of morbidity and death for both the mother and the foetus. The impact of climate change on a number of diseases, in particular hypertensive disorders in pregnancy (HDP), has become a major public health concern. The objective of this study was to determine the Effect of climate change on the prevalence of Hypertensive disorders in pregnancy and its complications. Methods: retrospective cross-sectional study was carried out at the department of obstetrics and gynecology, Aga Khan secondary hospital, Hyderabad from 2019 to 2023 after taking permission from the ethical committee of the institute. Data was collected by reviewing hospital records of the patients delivered during the study period. Seasonal changes included in the study were extremes of weather, including summer (May, June, July, august) and Winter (Nov, Dec, Jan, Feb), the extreme temperature during these months, and the temperature on the day the patients presented to our hospital were recorded from the data taken from the Regional Meteorological department, Karachi. The collected data were analyzed by SPSS software version 26. Frequency and percentages were calculated for booking status, PIH, Pre-eclampsia, mode of delivery, seasonality, and fetal outcomes. Results: In the current retrospective study the medical records of 15928 pregnant women were reviewed from 2019 to 2023 to the determine hypertensive disorders in pregnancy in the department of obstetrics and gynecology, Aga Khan secondary hospital, Hyderabad. The overall prevalence of hypertension was 932 (5.85%). Pregnancy-Induced Hypertension was found to be the most prevalent condition, affecting 57 % of the total study population followed by Preeclampsia 42.90%. Out of the total participants 686(73.59%) underwent caesarean sections while 246(26.41%) had normal vaginal deliveries. The participants were categorized based on their exposure to varying climatic conditions, particularly seasonal temperature fluctuations. Hypertensive disorders were more common in summer season as compared to winter season during the study period. Conclusion: The current study concluded that the prevalence of hypertension disorders and the problems they cause during pregnancy have been significantly affected by climate change.